Seni Grafis : Visualisasi Aktivitas Pandai Besi di Nagari Sungai Puar dengan Teknik Relief Print - Rafiqi Rafiqi; Yofita Sandra (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
This final work aims to contribute to the preservation of local culture, as well as introducing graphic art as a means of telling stories and depicting community life, especially the activities of blacksmiths in Nagari Sungai Puar. Therefore, the author created a work entitled "graphic art: visualization of blacksmith activities in Nagari Sungai Puar using relief print techniques" and wanted to spread various elements in blacksmith activities, starting from the process of making tools and interactions between blacksmiths. The creation method used is the Halma Hawkins method through the stages of exploration, improvisation and formation. With this method, this work can later be visualized into a graphic art work using relief printing techniques. The final work product is ten works of graphic art measuring 55 x 40 cm which depict blacksmith activities in the Sungai Puar village. The works are entitled: Making a rod, Cutting iron, Burning furnace, Forging iron, Forming iron, Grinding a kite, Cooling a knife, Sharpening a knife, Skillful hands, Final stages.